Corseting: a new technique for the management of diffuse venous malformations in the head and neck region. Issue 12 (December 2018) - Nair, S.C.; Chawla, J.P.; Shroff, S.S.; Kumar, B.; Shah, A.
Abstract: A new surgical technique of intra-tumoural ligation for the treatment of low-flow vascular malformations in the head and neck region is proposed. Ninety patients with diffuse low-flow vascular malformations diagnosed clinically and/or radiologically were treated surgically with the corset suturing technique. All patient records and clinical photographs were reviewed retrospectively. Significant clinical results were obtained: a reduction of the turnout tumour mass and a return of the regional facial outline was evident within 4 weeks after surgery. Recurrence of the lesion (seen in 10 patients) and transient facial nerve palsy (seen in seven patients) were the main complications. All incisions were placed within the junction lines of cosmetic subunits and skin tension lines of the head and neck. The advantages of this technique over the widely used and popular Popescu technique are discussed. Also, the indications, disadvantages, operative technique, and complications are described. In conclusion, corset suturing was found to be a simple, aesthetic, and cost-effective method of treating diffuse low-flow vascular malformations of the head and neck.